Structure and importance of soil-protecting forests in the areas administered by the RDSF Toruń - Wiśniewski, Paweł; Kistowski, Mariusz (Bulletin of Geography. Physical Geography Series, 2015)
The paper presents the state and importance of soil-protecting forests in the areas managed by the RDSF in Toruń, as well as changes in their structure over 29 years. The management of the RDSF in Toruń is characterized by a systematic increase in the area, thickness and rich abundance of soil-protecting forests, particularly intense since the mid-nineteen-nineties. They cover mainly rusty soils and podzols on outwash areas, sandy terraces in sloped areas of postglacial valleys and gullies as well. Soil-protecting forests, which are managed by the RDSF in Toruń, vary a great deal considering their habitat, both in terms of dampness and trophic richness as well as spatially. The dominance of coniferous forests is due to the fact that they grow in the poorest habitats, which have not been previously used for agricultural purposes, and to the common practice in recent years of pine reforestation in open stromal areas. The assessment of the state of habitats indicates that 66.2% of the soil-protecting forest area is characterized as natural and close-to-natural. Distorted or transformed habitats occupy 26.2% of the soil-protecting forest area, while the degraded habitats 7.6%. Taking the study area into consideration we can observe the relationship between the incompatibility of habitat in its natural form and the post-arable feature. Changes in habitat characteristics are shown by 75.5% of the area of the soil-protecting forest located on former farmland, mainly in the areas with rusty podzolic soils (Albic Brunic Arenosols). Incompatibility of the habitats is, among others, the result of the creation in recent years, during the afforestation of agricultural lands, of solid pine stands, also in fertile habitats. Secondary planted pine monocultures in the forest areas resulted in podzolization of rusty soils and transformed them into rusty podzolic soils.